Hubungan antara kualitas tidur dan kesejahteraan psikologis pada mahasiswa - Mustofa, Muhammad Royhan (Maliki Interdisciplinary Journal, 2025)
In Good sleep quality is an important factor in maintaining psychological well-being, especially for students who often face academic, social and emotional pressures. Poor quality sleep can negatively impact mental health, increasing the risk of stress, anxiety, mood disorders, as well as decreasing endurance and cognitive function. Sleep deprivation can also hinder students' ability to manage academic and interpersonal pressures, ultimately contributing to decreased learning motivation and academic performance. Conversely, adequate and quality sleep can improve concentration, emotional stability and overall well-being. Regular sleep patterns play an important role in maintaining hormonal balance and the nervous system, which contributes to increased resilience to stress and long-term happiness. Therefore, awareness of the importance of maintaining sleep quality needs to be raised so that students can achieve optimal psychological well-being. By adopting healthy sleep habits, students can improve their quality of life and ability to deal with academic and social challenges more effectively.